Broadband photodetector based on NiO/TiO2/n-Si heterojunction - Vincent Teng (Infrared Physics & Technology, 2024)
Broadband photodetector (PD) that can response to a broad spectrum from ultraviolet (UV) to near infrared (NIR) has attracted much research activities due to its many potential applications in a variety of fields, such as image sensing, optical communications, environmental monitoring, and day and night surveillance. In this work, a high-performance broadband PD based on NiO/TiO2/n-Si heterojunction is reported. The device consisted of a 2 nm TiO2 tunnelling layer, which was deposited by magnetron sputtering technique, between NiO and n-Si. The heterojunction photodetector (HPD) exhibits high sensitivity toward a broad spectrum from 341 to 1050 nm. It yields maximal responsivity of 1.47, 0.58, 0.82, 0.97, 1.62 and 1.21 A/W under 341, 365, 660, 850, 940 and 1050 nm illumination, respectively, at a bias voltage of −1 V. The corresponding detectivities are between 2.6 × 1011 and 7.3 × 1011 Jones. The external quantum efficiency (EQE) as high as 553 % indicates a remarkable gain of the HPD. Notably, the HPD shows self-powered characteristics with an ultrahigh responsivity of 1.15 A/W and detectivity of 6.38 × 1012 Jones. In addition, the fast response speed of less than 0.1 s is obtained under zero bias. The results demonstrate the development of low-cost, self-powered and high-performance silicon based broadband HPD.